ANALYSIS OF KNOWLEDGE AND ATTITUDES REGARDING PAIN MANAGEMENT IN NURSES WORKING IN NEONATAL UNIT - LATIF, Z; QASIM, S (Biological and Clinical Sciences Research Journal, 2024)
Effective neonatal pain management is crucial in Neonatal Intensive Care Units (NICUs), yet gaps in knowledge and attitudes among nursing staff can impact the quality of care. Understanding these gaps is essential to developing strategies for improved training and patient care outcomes. Objective: To assess the knowledge and attitudes regarding management in nurses working in neonatal ICU. Methods: The cross-sectional study was conducted in the Neonatal Intensive Care Unit Hospital from September 2023 to August 2024. A total of 100 neonatal nurses working in the NICU for at least a year were included in the study. Data was collected through a 42-item questionnaire divided into three sections. The first part included 10 questions about nurses’ demographics. The second part included 21 questions to inquire about knowledge of neonatal pain management which could be answered on a Likert scale from 1 to 5 with being strongly disagree and 5 being neutral. The last sections included 11 questions to assess nurses’ attitudes regarding the subject which could be responded to on a Likert scale. Results: Nurses had a poor knowledge level regarding neonatal pain management. 92% of nurses were capable of identifying a neonate in pain, however, 30% wrongly agreed that neonatal pain response was less than adults. 32% of nurses were of the perspective that parents should not be present during invasive procedures. 50% of nurses wrongly thought of sedation as the best pain relief. More than 80% of nurses were positive about palliative care for chronically ill neonates. However, 45% of nurses did not think that surgeries and invasive procedures should ease neonatal pain. Conclusion: Poor knowledge and moderately satisfactory attitude were noted in neonatal nurses regarding neonatal pain management. Improvement in awareness programs and training is urgently needed to improve patient care.